International cooperation on climate-friendly technologies - Rolf Golombek; Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2009)
We examine international cooperation on technological development as a supplement to, or an alternative to, international cooperation on emission reductions. R&D should be increased beyond the non-cooperative level if (i) the technology level in one country is positively affected by R&D in other countries, (ii) the domestic carbon tax is lower than the Pigovian level, or (iii) the domestic carbon tax is set directly through an international tax agreement. A second-best technology agreement has higher R&D, higher emissions, or both compared with the first-best-outcome. The second-best subsidy always exceeds the subsidy under no international R&D cooperation. Further, when the price of carbon is the same in the second-best technology agreement and in the case without R&D cooperation, welfare is highest, R&D is highest and emissions are lowest in the second-best R&D agreement.
Keywords: H23; O30; Q20; Q38; Q48; Q54; 330; climate policy; international climate agreements; R&D policy; technology spillovers; Klimaschutz; Umwelttechnik; Internationale technische Zusammenarbeit; Forschungskooperation; Umweltabkommen; Forschungs- und Technologiepolitik; Spillover-Effekt; Umweltökonomik; Theorie